Effects of hot extrusion deformation on microstructure and mechanical properties of the spray-deposition 17 vol.% SiCp/7055Al composite. (20th July 2021) - Tang, Binbin; Jiang, Xianquan; Jin, Peipeng; Wang, Haitao; Peng, He
Abstract: In this study, the microstructure evolution and mechanical properties under hot extrusion of 17 vol.% SiCp/7055Al composite fabricated through the spray-deposition was investigated by employing the Microscope (SEM), the x-ray diffraction (XRD) and the electron back scattering diffraction (EBSD) under a range of deformation conditions. The extrusion temperature reached 400 °C, 450 °C, 500 °C, and the extrusion ratio was at 9, 13, 20 respectively. As revealed from the results the microstructure evolution and mechanical properties of the composite were affected by the extrusion and the precipitated phase. As indicated from the Optical microscope (OM) and the EBSD analysis, the structure variation of the hot extrusion deformation at 450 °C was mainly the dynamic recovery (DRV). However, the dynamic recrystallization (DRX) was dominating at the extrusion temperature of 500 °C and a ratio of 20. In the DRX process, the dislocation substructures appeared within the grains, to reduce low angle grain boundaries (LAGBs) progressively. The textures with 110 ⟨111⟩ paralleling to TD and the recrystallization textures 001 ⟨100⟩ and 124 ⟨211⟩ were characterized. As indicated from the tensile tests, the extrusion eliminated the preparation defects and accommodated the thermal expansion (CTE) mismatch between the matrix and the SiC particles, thereby improving the performance of the composite.